Infrared light management using a nanocrystalline silicon oxide interlayer in monolithic perovskite/silicon heterojunction tandem solar cells with efficiency above 25% - Mazzarella, L; Lin, YH; Lin, YH; Kirner, S; Morales-Vilches, AB; Korte, L; Albrecht, S; Crossland, E; Stannowski, B; Case, C; Snaith, H; Schlatmann, R (Wiley, 2019)
Perovskite/silicon tandem solar cells are attractive for their potential for boosting cell efficiency beyond the crystalline silicon (Si) single-junction limit. However, the relatively large optical refractive index of Si, in comparison to that of transparent conducting oxides and perovskite absorber layers, results in significant reflection losses at the internal junction between the cells in monolithic (two-terminal) devices. Therefore, light management is crucial to improve photocurrent absorption in the Si bottom cell. Here it is shown that the infrared reflection losses in tandem cells processed on a flat silicon substrate can be significantly reduced by using an optical interlayer consisting of nanocrystalline silicon oxide. It is demonstrated that 110 nm thick interlayers with a refractive index of 2.6 (at 800 nm) result in 1.4 mA cm − ² current gain in the silicon bottom cell. Under AM1.5G irradiation, the champion 1 cm 2 perovskite/silicon monolithic tandem cell exhibits a top cell + bottom cell total current density of 38.7 mA cm −2 and a certified stabilized power conversion efficiency of 25.2%.